Efficacy of pharmacotherapy according to laser correlation spectrometry in elderly with arterial hypertension and comorbid pathology - Tofan, N. V.; Iablonska, V. B.; Khyzhnyak, O. V.; Nigreskul, O. Yu.; Novikov, S. A. (Journal of Education, Health and Sport, 2019)
In patients with arterial hypertension (AH) pharmacotherapy often remains ineffective because of comorbid pathology. Research of haemodynamic and homeostatic processes in such patients allows prescribe effective antihypertensive medicines, improve life quality and prognosis. Material and methods: 60 patients with AH, coronary artery disease and obesity were divided into three groups: 1st group was treated with lisinopril + atorvastatin + aspirin (regimen I); 2nd group was treated with lisinopril + atorvastatin + bisoprolol + aspirin (regimen II); 3rd group was treated with lisinopril + bisoprolol + indapamide + atorvastatin + aspirin (regimen III). Laser correlation spectrometry (LCS) was used to evaluate the homeostatic alterations. Results: All regimens were equally effective in normalization of systolic blood pressure and did not influence the ejection fraction. Only in the 3rd group was determined significant increase of glomerular filtration rate (92.732.12 vs 79.6213.62 ml/min/1.73m2). The LCS test showed that these patients had high level of light scattering particles IV, which may be caused by activation of anabolic processes. In other groups, spectral alterations were not so expressive. Conclusions: Prescription of antihypertensive therapy cause homeostatic and metabolic alterations, which may influence the efficacy of treatment.